6(2n+2)=6(6n+8)+9

Simple and best practice solution for 6(2n+2)=6(6n+8)+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(2n+2)=6(6n+8)+9 equation:


Simplifying
6(2n + 2) = 6(6n + 8) + 9

Reorder the terms:
6(2 + 2n) = 6(6n + 8) + 9
(2 * 6 + 2n * 6) = 6(6n + 8) + 9
(12 + 12n) = 6(6n + 8) + 9

Reorder the terms:
12 + 12n = 6(8 + 6n) + 9
12 + 12n = (8 * 6 + 6n * 6) + 9
12 + 12n = (48 + 36n) + 9

Reorder the terms:
12 + 12n = 48 + 9 + 36n

Combine like terms: 48 + 9 = 57
12 + 12n = 57 + 36n

Solving
12 + 12n = 57 + 36n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-36n' to each side of the equation.
12 + 12n + -36n = 57 + 36n + -36n

Combine like terms: 12n + -36n = -24n
12 + -24n = 57 + 36n + -36n

Combine like terms: 36n + -36n = 0
12 + -24n = 57 + 0
12 + -24n = 57

Add '-12' to each side of the equation.
12 + -12 + -24n = 57 + -12

Combine like terms: 12 + -12 = 0
0 + -24n = 57 + -12
-24n = 57 + -12

Combine like terms: 57 + -12 = 45
-24n = 45

Divide each side by '-24'.
n = -1.875

Simplifying
n = -1.875

See similar equations:

| 7(2+x)=39+5(x-2) | | X-9+4= | | 144=9(n+1) | | X-6+2x-4= | | 10m+6-6= | | 20Q-2Q^2=4+2Q^2 | | 5p-7+3p= | | 4/3x=-1 | | 4q^2-20q+4=0 | | (x+8)(x+8)=25 | | 14/5x=1 | | -3p-2(6-5p)=3(p-2)-14 | | (x+8)(x+8)=-25 | | (x-2)(x-2)=64 | | 12(z+1)-4(2-2)=4(z-4)+3(2-4) | | 2x^2-2+130=0 | | v^2-5v=-4 | | -14-5(x+2)=2x-6(x+3) | | 10(x+1)=0 | | 3x+7x+11=3x+25 | | 8v-24=432 | | 3x-15=6x-9y | | 13+17m-8= | | 1/5x=x-12 | | 5h+2(11-h)=15 | | 5(x-1)=65 | | 11w+12w-7+5=-3w+5-7 | | 11w+21(3w-1)=15w | | 2-1/7x=4 | | 3+12x-5=22 | | 25(4x+2)=150 | | 8x+3y-5x+7-10y+2= |

Equations solver categories